2022
DOI: 10.1136/rmdopen-2022-002593
|View full text |Cite|
|
Sign up to set email alerts
|

Acceptable risks of treatments to prevent rheumatoid arthritis among first-degree relatives: demographic and psychological predictors of risk tolerance

Abstract: ObjectivesTo quantify tolerance to risks of preventive treatments among first-degree relatives (FDRs) of patients with rheumatoid arthritis (RA).MethodsPreventive treatments for RA are under investigation. In a preference survey, adult FDRs assumed a 60% chance of developing RA within 2 years and made choices between no treatment and hypothetical preventive treatment options with a fixed level of benefit (reduction in chance of developing RA from 60% to 20%) and varying levels of risks. Using a probabilistic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
2
2
0
Order By: Relevance
“…Respondents more likely to choose the no-treatment option also agreed less with the statement that smoking causes lung cancer and were less sure of their personal risk compared with an average person who smokes. Similar to our findings, Simons et al found that approximately 14% of respondents would likely choose no treatment when presented with a hypothetical preventive rheumatoid arthritis treatment and that preferences for no treatment were associated with lower perceived chance of developing the disease. Future qualitative research should explore the reasoning behind opting out of preventive care to better understand these preferences.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Respondents more likely to choose the no-treatment option also agreed less with the statement that smoking causes lung cancer and were less sure of their personal risk compared with an average person who smokes. Similar to our findings, Simons et al found that approximately 14% of respondents would likely choose no treatment when presented with a hypothetical preventive rheumatoid arthritis treatment and that preferences for no treatment were associated with lower perceived chance of developing the disease. Future qualitative research should explore the reasoning behind opting out of preventive care to better understand these preferences.…”
Section: Discussionsupporting
confidence: 89%
“…Respondents more likely to choose the no-treatment option also agreed less with the statement that smoking causes lung cancer and were less sure of their personal risk compared with an average person who smokes. Similar to our findings, Simons et al 16 found that approximately 14% of respondents would h Reference group is those who believe their self-risk of getting lung cancer without treatment is the same as the average person who smokes in the US.…”
Section: Jama Network Open | Oncologysupporting
confidence: 91%
See 1 more Smart Citation
“…This would mean the outputs can be reused to raise awareness about treatment important differences and their potential impact in treatments available to patients. Final workshop participants had a range of numeracy levels, and their average was in line with other general population groups [ 30 ], however we had a lower proportion of participants with low numeracy when compared with general research participants [ 31 , 32 ]. Given art-based methods such as the creative workshops are expected to make research topics more accessible [ 12 ], future work should focus on recruiting a larger proportion of participants with low numeracy levels and explore the role and impact creative workshops can have on their involvement in numerical aspects of research.…”
Section: Discussionmentioning
confidence: 56%